P. Duchliński, A. Kobyliński, R. Moń, E. Podrez, Etyka a problem nihilizmu, Wydawnictwo Naukowe Akademii Ignatianum, Kraków 2019, ss. 259 .. - Mietelski, Tymoteusz (Warszawskie Studia Teologiczne, 2020)
The article shows the main theses of the book by P. Duchliński, A. Kobyliński, R. Moń, E. Podrez, Etyka a problem nihilizmu, Wydawnictwo Naukowe Akademii Ignatianum, Kraków 2019, pp. 259. It presents the methodology of research resulting in this book. It acquaints with its structure. It assesses whether the authors have achieved the intended goal, but also points to the weaknesses of the publication.